Understanding the Dimensions of Kindergarten Teachers' Burnout: Scoping the Factors and Its Strategic Preventions - Condiman, Liza C (PPSDP International Journal of Education, 2024)
This qualitative phenomenological study aims to explore the challenges encountered by kindergarten teachers. Purposive sampling technique was employed to select 10 kindergarten teachers from Carmen District, Mangalcal. Semi-structured interviews were conducted to gather rich and detailed accounts of the participants' experiences. The thematic analysis revealed three major challenges encountered by kindergarten teachers: physical tiredness, difficulty dealing with toddlers, and managing undisciplined learners. Additionally, three predominant coping mechanisms emerged: taking short vacations, seeking assistance from co-workers, and developing a supportive environment. Furthermore, teachers' insights and realizations in connection with feeling tired and burned out were categorized into themes of learning to set boundaries and focusing on the day's work.This study contributes to the understanding of the challenges faced by kindergarten teachers in a specific geographical context and provides insights into their coping mechanisms and reflections on burnout.